Long-term dynamics of forage base and food supply for nekton in the upper epipelagic layer of the western Bering Sea. Part 1. Composition and abundance of zooplankton and small-sized nekton - S. V. Naydenko; A. A. Somov; N. A. Kuznetsova; M. A. Shebanova (Известия ТИНРО, 2022)
An updated concept for the state, dynamics, and production of plankton communities in the upper epipelagic layer of the western Bering Sea is presented based on the timeseries for 1986–2020. The zooplankton biomass in summer exceeded the biomass in fall season in 1.3–2.1 times for the layer of 0–50 m and in 1.1–1.8 times for the layer of 0–200 m, mostly because of decreasing abundance of copepods and chaetognaths that was not compensated by slight increase of the euphausiids and amphipods biomass. Interannual variations were higher and reached 2–3 times and 4–5 times, respectively. Abnormal blooming of certain ecological groups of zooplankton (either warm-water or cold-water) occurred in the anomalous years. Species structure of zooplankton community varied in dependence on oceanographic conditions, generally toward higher abundance in warmer environments. In spite of considerable impact of thermal regime, this dependence was not close and even was absent in some cases that indicated a complex organization of zooplankton communities subjected to influence of many environmental factors. Mean total biomass of large-sized zooplankton and micronekton (prey for large-sized nekton) in the upper epipelagic layer of the western Bering Sea is estimated as 41 . 106 t in summer and 24 . 106 t in fall season, its total production as 101 . 106 t and 67 . 106 t, respectively. In summer, production of non-predatory zooplankton (phyto- and euryphages) prevailed over the predatory zooplankton production, with exception of 2009 and 2013. On the contrary, production of zoophages prevailed in autumn due to successive seasonal changes in the epipelagic plankton communities. These modern data on biomass and production of the zooplankton communities indicate significant reserves of food resources for fish and squids in the deep-water Commander Basin, western part of the Aleutian Basin, and in the area at Cape Navarin.